Tindak Tutur Direktif dalam Novel Azzamine Karya Sophie Aulia - Shelsa Alya Yosta; Ermanto (Persona: Kajian Bahasa dan Sastra, 2024)
This study aims to describe: (1) the types of directive speech acts in the novel Azzamine by Sophie Aulia. (2) the strategy of directive speech action in the novel Azzamine by Sophie Aulia. (3) the function of directive speech in the novel Azzamine by Sophie Aulia. The object of this research is Sophie Aulia's novel Azzamine which was published in 2022. "Directive speech can be seen in direct communication and can also be seen in a written book in the form of a novel. As a fictional writing, the novel shows the storyline through dialogue between characters. Dialogue in a novel is a form of speech in a certain unique situation or position of speech. This study was conducted to describe (1) the types of directive speech acts in the novel Azzamine by Sophie Aulia, (2) the strategy of directive speech actions in the novel Azzamine by Sophie Aulia, and (3) the function of directive speech acts in the novel Azzamine by Sophie Aulia. This research is a qualitative research using the description method. The data source used in this study is the dialogue of all the characters in Sophie Aulia's novel Azzamine which contains directive speech. The data collection technique in this study, the researcher utilizes the corpus linguistic method using Kortara for data collection and classifies the amount of data that is believed to be included in the act of directive speech. Data analysis is carried out in several steps as follows: (1) identifying data classified as a type of directive speech act using the KORTARA application, (2) classifying data based on research objectives, (3) analyzing the classified data, (5) formulating conclusions from the analysis results. Based on data analysis, three research findings were found. First, there are 5 types of directive speech acts, namely, directive speech acts of instructing, directive speech acts of probing, directive speech acts of demanding, and directive speech acts of defiance. The most dominant directive speech is the directive speech act of ordering and the least used is the act of challenging directive speech. Second, five speaking strategies, namely, "speaking frankly without further ado (BTTB), speaking frankly with positive politeness (BBKP), speaking frankly with negative politeness (BTBKN), vague speaking strategy (BSS), and speaking in the heart or silence (BDH). The most dominant speaking strategy is the strategy of speaking frankly without further ado (BTTB) and the least used is the strategy of speaking in the heart or silently (BDH). Third, the four functions of directive speech acts, namely, competitive functions, convivial functions, collaborative functions, and conflictive functions. The most dominant function of directive speech is the competitive function and the least used is the collaborative function, and the conflictive function.